Perbedaan Kecemasan Menulis Siswa Berdasarkan Pengalaman Menulis - Irma Safiah Lubis; Salman Munthe; Yuda Syahputra (SAP (Susunan Artikel Pendidikan), 2022)
Indonesia is the 4th most populous country in the world after China, India and the United States. So that Indonesia is included in one of the developing countries in the world. However, in scientific publications, Indonesia ranks 48th in the world. This encourages researchers' interest in assessing the psychological condition of Indonesian university students in writing, because writing skills are not only cognitive but also emotional activities. The purpose of this study was to describe the anxiety conditions of students at MTs Negeri 2 Medan in writing and to examine the differences between experienced and non-experienced students. This type of research is descriptive, the research sample is 362 students consisting of 17.9% male and 82.1% female. The data was collected using a writing apprehension scale, consisting of 26 statements of anxiety about writing in general that were given online. The research data were analyzed using the Rasch model by testing variable maps, and subtotal specifications. The findings discovers that students who have never written will experience more writing anxiety than students who have had writing experience. In addition, teacher feedback is also one of the factors that influence students' writing anxiety, negative reactions by teachers and continuing to blame students will affect students' writing experiences in the future.